2014
DOI: 10.19123/eixo.v3i1.141
|View full text |Cite
|
Sign up to set email alerts
|

Levantamento Histórico E Relatos De Inundações Do Córrego Do Gregório Na Região Central Do Município De São Carlos - Sp

Abstract: O crescimento das cidades ocorrido nas últimas décadas transformou o Brasil em um país essencialmente urbano (83% de população urbana) (TUCCI, 2008). Grande parte desse crescimento deu-se, e ainda se dá, de forma desordenada e sem planejamento, em que parte da população acaba ocupando áreas ambientalmente frágeis e com topografia inapropriada para construir (áreas de encosta e de inundação de corpos hídricos, por exemplo). Nesse contexto, destacamos as inundações, que representam o transbordamento das águas de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…In contrast, in a study in in Champaign-Urbana, Illinois, in the USA, Cadavid and Ando (2013) found that depending on the location two types of situation may happen, people may be more willing to pay if they are suffering from floods, or worry less about flooding because they got used to it. In the city of São Carlos, for example, the shopkeepers in a historical flood prone area have a sense of belonging to the place and are not willing to relocate (Marotti et al, 2014;Mendes and Mendiondo, 2007). This information can help decision makers to offer public incentives to implement stormwater BMPs at small or lot scales.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in a study in in Champaign-Urbana, Illinois, in the USA, Cadavid and Ando (2013) found that depending on the location two types of situation may happen, people may be more willing to pay if they are suffering from floods, or worry less about flooding because they got used to it. In the city of São Carlos, for example, the shopkeepers in a historical flood prone area have a sense of belonging to the place and are not willing to relocate (Marotti et al, 2014;Mendes and Mendiondo, 2007). This information can help decision makers to offer public incentives to implement stormwater BMPs at small or lot scales.…”
Section: Discussionmentioning
confidence: 99%
“…Tal restrição se deve à passagem obrigatória do córrego do Monjolinho pelo canal existente sob a linha férrea, que vem propiciando inundações frequentes na região. Muitos estudos sobre o sistema de drenagem da cidade de São Carlos (BARBASSA, 1991;BORGES, 2006;MENDES;MENDIONDO, 2006;DECINA, 2012;MAROTTI et al, 2014) e projetos de alteração já foram desenvolvidos, sem que se pudesse contar com curvas-chave de pontos notáveis da rede de córregos que atravessam a cidade.…”
Section: Lista De Tabelasunclassified